A rock damage constitutive model and damage energy dissipation rate analysis for characterising the crack closure effect. Issue 1 (2nd January 2018) - Wen, Tao; Liu, Yourong; Yang, Chenggang; Yi, Xianlong
ABSTRACT: Due to the insufficiency of the previous damage constitutive model for rock, an improved damage mechanics model for rock is proposed with characterising the crack closure effect. Otherwise, the effective methods of determining the model parameters and crack closure coefficient are proposed. The results represent that the model can reflect the damage evolution of rocks in the deformation process in the crack closure stage and this improved model is more reasonable than the previous model. Crack closure coefficient also has great effect on distribution parameters. The calculation formula of damage energy dissipation rate considered that crack closure effect is derived and the relationships between damage energy dissipation rate and crack closure coefficient are analysed. Crack closure coefficient has great effect on damage dissipation energy rate. Damage energy dissipation rate increases with the decrease of crack closure coefficient and damage energy dissipation rate increases quickly in the post-peak stage.